2014
DOI: 10.1016/j.tins.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Local versus global scales of organization in auditory cortex

Abstract: Topographic organization is a hallmark of sensory cortical organization. Topography is robust at spatial scales ranging from hundreds of microns to centimeters, but can dissolve at the level of neighboring neurons or subcellular compartments within a neuron. This dichotomous spatial organization is especially pronounced in the mouse auditory cortex, where an orderly tonotopic map can arise from heterogeneous frequency tuning between local neurons. Here, we address a debate surrounding the robustness of tonotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 90 publications
(104 reference statements)
6
93
0
Order By: Relevance
“…We confirmed a heterogeneous organization of the Au1 in both anesthetized and awake mice as described previously using OGB-1 or fluo-4 [9,15]. Therefore, our results with Cal-520 AM support the hypothesis of heterogeneity of the topographic organization in L2/3 local circuits in the Au1 [22], and provide a proof-of-principle for the use of Cal-520 for Au1 mapping experiments.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We confirmed a heterogeneous organization of the Au1 in both anesthetized and awake mice as described previously using OGB-1 or fluo-4 [9,15]. Therefore, our results with Cal-520 AM support the hypothesis of heterogeneity of the topographic organization in L2/3 local circuits in the Au1 [22], and provide a proof-of-principle for the use of Cal-520 for Au1 mapping experiments.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…The inconsistent results in previous two-photon imaging-based mapping experiments in the Au1 can be explained by various reasons, including differences in recorded cortical areas, cortical layers, experimental methodologies, and species and brain states [22]. Among these reasons, the use of different indicators might be animportant possibility, although this aspect seems to be often ignored in the community.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thereby, the presented synaptic population data of individual input systems is in accordance with recent anatomical findings [61]. Further, data from 2-photon imaging of single-cell spectral responses showed that is depends on laminar depth, afferent or intracortical inputs and hence the cortical processing hierarchy [16,17,62,63]. Corticocortical integration in neurons mainly receiving broad corticocortical inputs might hence contribute to the perceptual robustness across sound levels based on population coding [9,10,15].…”
Section: Discussionsupporting
confidence: 83%
“…Although we detect refinement of L2/3 to L4 connections, intralaminar connections within L4 were not changed. Neighboring L4 neurons show higher similarity in their frequency selectivity than L2/3 neurons (Bandyopadhyay et al, 2010, Winkowski and Kanold, 2013, and Kanold et al, 2014), suggesting that the refinement we observe in L2/3 decreases connections between neurons of different frequency selectivity. Together with the strengthening of thalamocortical connections to L4 neurons after DE (Petrus et al, 2014), this indicates that DE causes a remodeling of all inputs to L4 neurons in A1 to improve sound processing.…”
Section: Discussionmentioning
confidence: 72%